Pengaruh Sistem Agroforestri Terhadap Pendapatan Anggota Kelompok Pengelola Hutan Kemasyarakatan Bu’u Bei di Desa Tina Bani Kecamatan Ende Kabupaten Ende - Elfrida Kastila Ine Tiga; Lusia Sulo Marimpan; Astin E. Mau; Nixon Rammang (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
Agroforestry is a land management system that combines forestry and agricultural/plantation crops with livestock in one land plot. Agroforestry systems have been applied in East Nusa Tenggara, one of which is in the Bu'u Bei Community Forest (HKm), Tina Bani Village, Ende District, Ende Regency. This study aims to determine the pattern/system of agroforestry applied and the contribution of agroforestry to the income of members of the HKm Bu'u Bei management group. This research was conducted on April 18-May 18, 2024. The sampling method used in this study is the census method with a total of 47 households. The data analysis used is descriptive and quantitative analysis methods. The results of the research obtained from the interview showed that 1) The application of cropping patterns on agroforestry land in Tina Bani Village only found one agroforestry system, namely the agrisilviculture system with a random mix cropping pattern (Random Mixture). 2) The contribution of agroforestry to the income of members of the Bu'u Bei HKm management group in 2023 amounted to 98.87% or around Rp 501,323,500 / year from the total household income.